Transformative Sufism of KH. Abdurrahman Wahid - Nurhidin, Edi; Naim, Ngainun; Dinana, Muhammad Fahim (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2022)
This paper observes the idea of Abdurrahman Wahid's Sufism. It is important to study Sufism in the reinforcement of dual morality in Indonesian Muslims. It is to complement the development of contemporary Sufism discourse in the archipelago as well. The research method used in this paper was a literature review. The data used in this paper were the works of Abdurrahman Wahid in the form of a collection of articles, bookkeeping of 'preface', and 'preface' which were scattered in several other people's books as well as other relevant writing sources. The data collected were then analyzed using a qualitative content analysis method, according to the topic of the writing. The results of research revealed that Abdurrahman Wahid's idea of Sufism contributed significantly to the realization of the basic values and teachings of Islam in the life of religion, society, nation, and state. It indicates that Abdurrahman Wahid has transformed the meaning of and actualized Sufism from and for Sufism. Love and compassion play a central role at the core of Sufism actively manifested in social life to fight for human values and principles. This research contributes to academic discourse by offering new perspectives on the integration of Sufism into modern social and political contexts. It highlights the relevance of Wahid's Sufism in addressing contemporary challenges such as interfaith relations, social justice, and national unity.